Human Type IV P-type ATPases That Work as Plasma Membrane Phospholipid Flippases and Their Regulation by Caspase and Calcium - Segawa, Katsumori (J Biol Chem, 2016)
In plasma membranes, flippases translocate aminophospholipids such as phosphatidylserine and phosphatidylethanolamine from the extracellular to the cytoplasmic leaflet. Mammalian ATP11C, a type IV P-type ATPase, acts as a flippase at the plasma membrane. Here, by expressing 12 human type IV P-type ATPases in ATP11C-deficient cells, we determined that ATP8A2 and ATP11A can also act as plasma membrane flippases. As with ATP11C, ATP8A2 and ATP11A localized to the plasma membrane in a CDC50A-dependent manner. ATP11A was cleaved by caspases during apoptosis, and a caspase-resistant ATP11A blocked apoptotic PtdSer exposure. In contrast, ATP8A2 was not cleaved by caspase, and cells expressing ATP8A2 did not expose PtdSer during apoptosis. Similarly, high Ca(2+) concentrations inhibited the ATP11A and ATP11C PtdSer flippase activity, but ATP8A2 flippase activity was relatively resistant to Ca(2+). ATP11A and ATP11C were ubiquitously expressed in human and mouse adult tissues. In contrast, ATP8A2 was expressed in specific tissues, such as the brain and testis. Thus, ATP8A2 may play a specific role in translocating PtdSer in these tissues.